Amide‐Catalyzed Phase‐Selective Crystallization Reduces Defect Density in Wide‐Bandgap Perovskites. Issue 13 (14th February 2018) - Kim, Junghwan; Saidaminov, Makhsud I.; Tan, Hairen; Zhao, Yicheng; Kim, Younghoon; Choi, Jongmin; Jo, Jea Woong; Fan, James; Quintero‐Bermudez, Rafael; Yang, Zhenyu; Quan, Li Na; Wei, Mingyang; et al.
Abstract: Wide‐bandgap (WBG) formamidinium–cesium (FA‐Cs) lead iodide–bromide mixed perovskites are promising materials for front cells well‐matched with crystalline silicon to form tandem solar cells. They offer avenues to augment the performance of widely deployed commercial solar cells. However, phase instability, high open‐circuit voltage ( V oc ) deficit, and large hysteresis limit this otherwise promising technology. Here, by controlling the crystallization of FA‐Cs WBG perovskite with the aid of a formamide cosolvent, light‐induced phase segregation and hysteresis in perovskite solar cells are suppressed. The highly polar solvent additive formamide induces direct formation of the black perovskite phase, bypassing the yellow phases, thereby reducing the density of defects in films. As a result, the optimized WBG perovskite solar cells (PSCs) ( E g ≈ 1.75 eV) exhibit a high V oc of 1.23 V, reduced hysteresis, and a power conversion efficiency (PCE) of 17.8%. A PCE of 15.2% on 1.1 cm 2 solar cells, the highest among the reported efficiencies for large‐area PSCs having this bandgap is also demonstrated. These perovskites show excellent phase stability and thermal stability, as well as long‐term air stability. They maintain ≈95% of their initial PCE after 1300 h of storage in dry air without encapsulation. Abstract : The highly polar solvent additive, formamide, enables phase‐selective crystallization in wide‐bandgap (WBG) perovskites. By suppressing the formation of non‐perovskite phases, the WBG perovskites ( E g ≈ 1.75 eV) exhibit excellent light‐induced phase, thermal, and air stability, as well as device performance with a high V oc of 1.23 V and reduced hysteresis, with a power conversion efficiency (PCE) of 17.8%.